STUDENTS` PERCEPTIONS ON THE USE OF POWERPOINT IN ENGLISH TEACHING AND LEARNING PROCESS AT SMAN 2 TAMBANG - Juliani, Rini; Azhar, Fadly; Mahdum, Mahdum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to investigate students’ perceptions on the use of PowerPoint in the English teaching and learning process at SMAN 2 Tambang. The research employed a descriptive quantitative design. The population consisted of 300 eleventh-grade students in the academic year 2024/2025, and 60 students from classes XI-9 and XI-10 were selected as the sample using cluster random sampling. The instrument used was a Likert-scale questionnaire consisting of 25 items developed based on five perception indicators: reception, evaluation, stimulus absorption, understanding, and judgment. The validity and reliability tests showed that all items were valid and highly reliable. The data were analyzed using descriptive statistics by calculating the mean score. The findings revealed that students had a positive perception of the use of PowerPoint in English learning. The highest mean score was found in the evaluation indicator, while the lowest was in the understanding indicator. Overall, PowerPoint was perceived as an effective, attractive, and supportive learning medium that enhanced students’ motivation, attention, and engagement in the classroom.